2015
DOI: 10.1088/1748-3182/10/2/026004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bio-inspired multilayer polarizers and their application to anti-counterfeiting

Abstract: Some insects, such as Papilio blumei and Suneve coronata, are known for exhibiting polarization effects on light such as color contrast or geometrical polarization rotation by reflection on their wing scales. The photonic structures found on these species that show these properties are multilayered spherical cavities or triangular grooves which polarize the light due to multiple inner reflections. These polarization effects, in addition to the intrinsic color-mixing properties of these photonic structures, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The structural coloration inspired by the wings of butterflies and beetles boasts optical properties such as iridescence, polarization caused by interference, scattering, and diffraction. In Figure , biologically inspired structures for structural coloration are anatomically categorized, depending on approach and process design from a single‐layer level, a multilayer level, a sculpture level, to a quasi‐ordered level . Textures on the layer itself, for example, holes, C‐grooves, and zigzags in Figure a, produce structural colors.…”
Section: Insect‐inspired Structural Colors For Imaging and Displaymentioning
confidence: 99%
See 2 more Smart Citations
“…The structural coloration inspired by the wings of butterflies and beetles boasts optical properties such as iridescence, polarization caused by interference, scattering, and diffraction. In Figure , biologically inspired structures for structural coloration are anatomically categorized, depending on approach and process design from a single‐layer level, a multilayer level, a sculpture level, to a quasi‐ordered level . Textures on the layer itself, for example, holes, C‐grooves, and zigzags in Figure a, produce structural colors.…”
Section: Insect‐inspired Structural Colors For Imaging and Displaymentioning
confidence: 99%
“…Textures on the layer itself, for example, holes, C‐grooves, and zigzags in Figure a, produce structural colors. Poncelet et al fabricated bioinspired cylindrical and triangle grooves for reproducing color contrast and polarization effect from the cuticle of Papilio blumei in Figure b . Umh et al reported nanobowl structures of TiO 2 , analogous to the cuticle of Cicindela oregona .…”
Section: Insect‐inspired Structural Colors For Imaging and Displaymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, multiple reflections would induce a geometric polarization rotation of the light which had been widely found in living organisms, such as the wing of Papilio butterfly [32]. Many efforts have been made on mimicking those structures, such as layer deposition techniques, conformal-evaporated-film-by-rota tion and lithography [33][34][35]. However, all those methods are high cost, difficult to prepare in large scale, and require complex manufacture process.…”
Section: Optical Properties Of Psmg Photonic Crystalmentioning
confidence: 99%
“…The phenomenon is attributed to the interference, diffraction and dispersion of light with facile periodic morphologies. [15][16][17] Materials with this characteristic have been widely used in many elds such as sensing, 18,19 bioassay, 20,21 anti-counterfeiting, 22 and optical components. 23 There are many materials with improved optical properties that have been developed and reported to obtain materials with structural colour, including silicon dioxide, polymethyl methacrylate and polystyrene, [24][25][26][27][28][29][30][31][32][33][34][35] since the fabrication of structural materials from colloidal spheres is low-cost and facile.…”
Section: Introductionmentioning
confidence: 99%